The Association between Body Mass Index and Lymph Node Harvest After Elective Colon Cancer Resections - Jose L. Cataneo; Hanna Meidl; Gaurang Joshi; Michael S. Zhang; Luke Willand; Rami Lutfi; Francisco Quinteros (World Journal of Colorectal Surgery)
Background: Obesity has been linked to the development of colorectal cancer and increase in morbidity. However, the impact body mass index (BMI) has on surgical staging through nodal harvest is not entirely understood. Objective: To identify the association between BMI and nodal harvest during elective colon cancer surgeries Design: Retrospective cohort review from 2015 to 2019. Setting: The National Surgical Quality Improvement Program-targeted colectomy database. Materials and Methods: The cohort was selected based on the codes corresponding to elective colectomies for colon cancer. BMI was grouped into the five clinically relevant categories and dichotomized. Nodal harvest was dichotomized into <12 and ≥12 lymph nodes. Univariate and multivariate regression analysis. Sample Size: A total of 35,039 patients. Main Outcomes Measures: The main outcome was adequate lymph node harvest for each BMI group. Secondary outcomes included analysis in laterality of tumors, approach, extent of resection, and identification of risk factors for adequate harvest. Results: The median BMI was 29.02 kg/m2 (interquartile range = 24.37–32.44) with a median of 22 (15–27) lymph nodes harvested. The BMI groups with the highest adequate lymph nodes harvested were those ≤25 with 93.7% compared to 92.8% in BMI >25 (P = 0.002). Right colon cancers had a higher rate of achieving adequate harvest than left colon cancers (94.8% vs. 90.8%, respectively; P < 0.001). Right tumors had a higher rate of adequate harvest in the ≤25 group, this frequency decreases as BMI increases and is the opposite for left tumors (P < 0.001). Inadequate harvest was higher for the open approach (9.82%) than that for laparoscopic (6.12%) or robotic (6.6%) procedures (P ≤ 0.001). BMI of ≤25 was associated with a 13% increase in the likelihood of an adequate nodal harvest (odds ratio = 1.13, 95% confidence index = 1.02–1.26). Conclusion: This study found that lower BMI was associated with a higher probability of achieving adequate nodal harvest. This can increase awareness about the risk of incomplete harvest in overweight and obese patients. Limitations: Large sample size bias, selection bias, and lack of details in specific variables due to the type of database.